Enhanced collection of phenotypic and engrafting human cord blood hematopoietic stem cells at 4°C. (4th July 2020) - Broxmeyer, Hal E.; Cooper, Scott; Capitano, Maegan L.
Abstract: The number of hematopoietic stem cells (HSCs) collected in cord blood (CB) at the birth of a baby is a limiting factor for efficacious use of CB in hematopoietic cell transplantation (HCT). We now demonstrate that collecting and processing of human CB at 4°C within minutes of the baby's birth results in significantly enhanced numbers of rigorously defined phenotypic HSC and self-renewing NSG immune-deficient mouse engrafting and SCID-repopulating cells. This was associated with decreased numbers of hematopoietic progenitor cells (HPC), as noted previously for hypoxia collected/processed cells blocking ambient air induced differentiation of HSC to HPC. We have thus defined a simple, cost-effective, means to collect increased numbers of CB HSC, of potential use for clinical CB HCT. : Abstract : This graphical abstract depicts results of collecting and processing human cord blood and mouse bone marrow hematopoietic stem (HSC) and progenitor (HPC) cells at 4°C vs. room temperature. Collecting/processing cells at 4°C mimics effects of that under hypoxia (3% O2 ).